Bentuk Penanaman Modal Asing Bangkok Bank Di Indonesia Berdasarkan Hukum Penanaman Modal - Sinulingga, Desi Ariani (Jurnal Hukum & Pembangunan, 2022)
Investment is part of the implementation of the country's economy which aims to increase national economic growth, create jobs, and encourage national economic development so that a prosperous, equal, and prosperous society can be realized. Investment regulation in Indonesia has been started since the issuance of Act Number 1 of 1967 concerning Foreign Investment and Act Number 6 of 1968 concerning Domestic Investment. Both regulations have been revoked by Act Number 25 of 2007 concerning Investment, and part of the provisions have been amended by the Omnibus Act Number 11 of 2020 concerning Job Creation. Foreign investment in Indonesia can be implemented in various ways. One of the sectors that is very open to foreign investment is the banking sector. On 20 May 2020, Bank Public Company Limited (“Bangkok Bank”) made foreign investment in Indonesia through the takeover or acquisition of shares of Bank Permata, which was previously owned by PT Astra International Tbk and Standard Chartered by 89.12%. Bangkok Bank is a limited liability company with the status of a public company engaged in banking and established in Thailand. The presence of Bangkok Bank in Indonesia began in 1968 by establishing a branch office in Indonesia, namely Bangkok Bank Indonesia.